Impact of Online Learning on Medical Education of Master Students - Komilova M.O.; Urakova Z.U. (Zien Journals, 2023)
In recent years, after the pandemic, online learning has become very relevant, and the use of distance learning in medicine is becoming a reality. Many students today consider this form of education as an alternative to the usual one, not only when receiving a second education, advanced training, but also choose this way to receive their first higher education. This article provides the results of an analysis of the impact of distance learning on the quality of education in medicine, on the health and performance of students in medical institutions, based on the analysis of a survey of master students.
Keywords: Medical Education; Distance Learning; Medical Students